2014
DOI: 10.2147/ppa.s67767
|View full text |Cite
|
Sign up to set email alerts
|

Motivations toward smoking cessation, reasons for relapse, and modes of quitting: results from a qualitative study among former and current smokers

Abstract: BackgroundSmoking cessation plays a crucial role in reducing preventable morbidity and mortality and is a recognized public-health-policy issue in many countries. Two of the most important factors that affect the efficacy of quitting smoking are motivation and the ability to cope with situations causing relapse.AimThe objective of the study reported here was to investigate former and current smokers’ motivations for smoking cessation, reasons for relapse, and modes of quitting.MethodsWe arranged four focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
67
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 47 publications
14
67
1
2
Order By: Relevance
“…Consistent with our findings of family member’s influence, prior studies have noted the importance of social influences in smoking cessation, such as family members urging the smoker to quit or informal bans on smoking at home [24, 25]. Christakis and Fowler [26] applied a network analysis approach to examine social influences on smoking behavior among a Framingham Heart Study cohort (from 1971 to 2003).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with our findings of family member’s influence, prior studies have noted the importance of social influences in smoking cessation, such as family members urging the smoker to quit or informal bans on smoking at home [24, 25]. Christakis and Fowler [26] applied a network analysis approach to examine social influences on smoking behavior among a Framingham Heart Study cohort (from 1971 to 2003).…”
Section: Discussionsupporting
confidence: 83%
“…A 2006 review of 30 studies examining smokers’ reasons for quitting found health consequences of smoking to be the most consistent motivation [23]. A 2014 qualitative study corroborated findings that concerns about health were one of the most important motivations to quit [24]. …”
Section: Discussionmentioning
confidence: 93%
“…Women in general usually are more concerned about health than men are, and pregnancy is one of the motivations in female smokers to quit smoking [50,51], reflecting the concern for their child’s health. However, the high rate of SHS found in pregnant and postpartum women in this study could reflect that although this vulnerable group might be very careful about health risks and protective of their child, SHS in their daily environment is very difficult for them to avoid.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that younger women were more likely to initiate screening themselves than older women and that women ≥70 years of age who were past, but not current, smokers were more likely to seek out screening on their own. Since these women were not current smokers, it is possible that they requested this test because they were concerned about their health (Buczkowski et al, 2014), but had limited understanding of its risk-benefit ratio. This suggests that patient education needs to target this population to prevent overutilization of health care resources.…”
Section: Discussionmentioning
confidence: 99%